Biocomputing 2001 2000
DOI: 10.1142/9789814447362_0010
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Non-Folding Problem: Amino Acid Determinants of Intrinsic Order and Disorder

Abstract: To investigate the determinants of protein order and disorder, three primary and one derivative database of intrinsically disordered proteins were compiled. The segments in each primary database were characterized by one of the following: X-ray crystallography, nuclear magnetic resonance (NMR), or circular dichroism (CD). The derivative database was based on homology. The three primary disordered databases have a combined total of 157 proteins or segments of length à "à vuà ' à rvqrà uvyrà urà qrvhvrà qhhihrà … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
209
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(226 citation statements)
references
References 26 publications
16
209
0
1
Order By: Relevance
“…4 the mutability of each amino acid residue were studied. As reported earlier, the computed amino acid substitution matrix coincides with the favorable amino acids proposed by Williams et al [18]. Substitution of amino acids by disfavorable residue to a preferred residue yields a large negative score in the substitution matrix.…”
Section: B Hubsm: a Substitution Matrix For Hub Proteinssupporting
confidence: 83%
See 3 more Smart Citations
“…4 the mutability of each amino acid residue were studied. As reported earlier, the computed amino acid substitution matrix coincides with the favorable amino acids proposed by Williams et al [18]. Substitution of amino acids by disfavorable residue to a preferred residue yields a large negative score in the substitution matrix.…”
Section: B Hubsm: a Substitution Matrix For Hub Proteinssupporting
confidence: 83%
“…Also these amino acids evolve at a different mutation rate [17]. Amino acids of disorder region lacks hydrophobic amino acid, contains more hydrophilic and charged residues [18] and, the low complexity region is enriched with cysteine and glutamine amino acids [19].…”
Section: Abstract ---mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it was confirmed that some disordered proteins can also be involved in several diseases such as Alzheimer disease, Parkinson disease and certain types of cancer (Williams et al, 2001;Galzitskaya et al, 2006) Therefore, studies on structural identification of intrinsically disordered proteins have been thought to be an aid in drug design, protein expression and functional recognition. Due to their significance, dealing with structural identification of the proteins that was named as "The Protein Non-Folding Problem" has gained growing interest in structural bioinformatics (Li et al, 2000).…”
Section: Introductionmentioning
confidence: 99%